Management of Eucalyptus short-rotation coppice and its outcome on fuel quality - Eufrade-Junior, Humberto de Jesus [UNESP]; Guerra, Saulo Philipe Sebastião [UNESP]; Sansígolo, Cláudio Angeli [UNESP]; Ballarin, Adriano Wagner [UNESP] (My University, 2018)
Earlier experiments with young Eucalyptus short-rotation coppice (SRC) in tropical environment have not evaluated the quality of whole-tree biomass fractions, and as such their total energy potential is still unknown. As this system is managed with a higher planting density and fertilization level compared to conventional plantations, the quality of forest biomass needs to be assessed. Hence, the goal of this study was to analyze how the short-rotation coppice affected the quality of stem, branches, and leaves used for power generation. Samples were collected from high-density plantation of Eucalyptus at two years old, and the thermochemical properties were evaluated. Carbon and ash content were lower for the stem fraction in higher density of planting, although the higher heating value was not significantly different from each treatment. Overall, the fuel quality of whole-forest biomass was not influenced by management practices. Statistically significant differences were found only between the whole-tree fractions. Eucalyptus SRC provided biomass qualitatively close to that from conventional forest systems and has potential to be quickly and feasible energy option.
Keywords: Bioenergy; Biomass; Energy crops; Short rotation coppice; Thermochemical properties